Concomitant use of corticosteroids and immune checkpoint inhibitors in patients with hematologic or solid neoplasms: A systematic review. (December 2017) - Garant, A.; Guilbault, C.; Ekmekjian, T.; Greenwald, Z.; Murgoi, P.; Vuong, T.
Highlights: We reviewed clinical interactions between immune checkpoint inhibitors and corticosteroids. 27 articles relating to this question were identified. These articles were scored by a scale and deemed to carry a clinically acceptable risk of bias. Overall, no data on types of steroids and dose was found to clearly interfere with immunotherapy. Clarification of this issue is required to facilitate immune checkpoint inhibitor delivery. Abstract: Purpose: Clinical trials studying immune checkpoint inhibitors exclude patients on corticosteroids, due to the hypothesis that corticosteroids may antagonize immunotherapy. We performed a systematic review of the literature looking at the clinical outcomes of cancer patients treated with immune checkpoint inhibitors and concomitant corticosteroids. Methods: The following databases were searched for relevant studies: MEDLINE, Embase Classic + Embase, BIOSIS Previews, the Cochrane Database of Systematic Reviews, the CENTRAL Registry of Controlled Trials, Web of Science and Scopus. Abstracts from the meetings of the European Cancer Congress/European Society for Medical Oncology, the American Society of Clinical Oncology, the American Society of Hematology, the European Society for Radiotherapy & Oncology, the American Society for Radiation Oncology and the European Society for Radiotherapy & Oncology were manually searched. Two independent reviewers screened the references: case reports and articles with a low risk of bias were retained. Results: Following a retrieval of 14603 unique references, 140 abstracts were retained for review; 27 articles are in the final analysis. Although limited, the reviewed data suggests that the concomitant administration of corticosteroids and immune checkpoint inhibitors may not necessarily lead to poorer clinical outcomes. Conclusion: In our systematic review, there was no objective data on the exact types of corticosteroids and the dose threshold above which an interaction could be measured clinically. Consideration of stratified randomization and treatment sequence evaluations in prospective trials may clarify this challenging topic and perhaps improve patient access to immune checkpoint therapies.